UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETIL ASETAT DAUN SALAM (Syzygium polyanthum) DAN UJI BILANGAN PEROKSIDA-NYA TERHADAP MINYAK GORENG CURAH - Vritta Amroini Wahyudi Afifah Nuril Aini, Dian Puspita Ayu Ramadhanni Kumala Dewi (Universitas Muhammadiyah Malang, 2019)
Cooking oil is a necessity of the people of Indonesia that is always needed. Based on the stages of manufacture, oil is divided into two, namely branded oil and bulk oil. Until now, branded oil is still the main choice even though it is economically more expensive than bulk oil. This is related to the tendency of bulk oil to experience rancidity due to oxidation reactions. The quality of bulk oil can be scientifically improved by the addition of antioxidants. Commonly used antioxidants are synthetic antioxidants such as TBHQ. Natural antioxidants are less popular because they have only stalled in the study but have not been compared significantly with synthetic antioxidants. In this study, a research is used to find out the stability of bulk oil with the addition of bay leaf ethyl acetate fraction and as a comparison of the use of TBHQ. Analysis of antioxidant activity of DPPH method was also used to find out determine the relationship between the power of antioxidant activity with the quality of bulk cooking oil. The evaluation was performed on the addition of bay leaf extract with various concentrations treated on bulk oil by heating for 20 minutes using 90˚C temperature. The results showed that the bay leave ethyl acetate fraction has IC50 value of 19.473 ppm, so it can effectively reduce the number of peroxide. The smallest peroxide number was obtained at treatment P6 (1%) that is 5,304 meqO2 / kg, where TBHQ (0,2%) as comparison have value equal to 4,147 meqO2 / kg. This shows that the antioxidant activity is very strong in bay leaf significantly affect the inhibition of bulk oil destruction. Natural antioxidant from bay leaf can prevent bulk oil from oxidation as well as synthetic antioxidants, but safer than synthetic antioxidants.